(untitled) (Italian Journal of Public Health, 2009)
The former communist countries of Southeastern Europe (SEE) are undergoing a rapid process of transformation from state-enforced rigid economies to market-oriented societies. Compared with European Union, SEE countries are characterized by higher death rates including not only infant mortality and maternal death, but also cardiovascular mortality and injuries. Yet, there is no sufficient research in SEE countries directed towards gaining a clear understanding of the health effects of transition and the fluctuations in health outcomes. A general characteristic in almost all SEE countries relates to the comparable problems they face for engaging in research work which include: (i) lack of funds; (ii) lack of expertise, and; (iii) lack of “good data”. Nevertheless, there is an emergent need to improve research capacities in order to address and analyze on a scientific basis the health problems and challenges in SEE countries. From this point of view, the Forum for Public Health in South Eastern Europe (FPH-SEE: www.snz.hr/fph-see) seems a suitable network to promote, provide guidance and support different research activities and research projects in SEE countries. To increase the visibility of FPH-SEE network and to enhance its collaboration and active communication with European academic institutions and donors, it was decided to establish an office near the Department of International Health, Faculty of Health, Medicine and Life Sciences, Maastricht University, which will be responsible for the coordination of the research network for SEE countries. This will help to promote research funding and to develop and strengthen research capacities in the SEE region.